Pengaruh Word Of Mouth dan Switching Cost Terhadap Keputusan Pembelian dan Loyalitas - Iha Haryani Hatta; Setiarini Setiarini (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
The reciprocal of WOM (word of mouth) & switching cost into purchasing and loyality. The purpose of research The affect WOM and switching cost of the decision to purchase & loyalty; The affect the decision to purchase of loyalty . The population this research are 200 Meat Me Café & Butchery’s customers in jakarta who were randomly selected by mixed data with SEM, AMOS21 program . The results of research explained that WOM and switching cost are influential decision to buy & loyalty, and the decision to buy influences loyalty. The WOM & switching cost substantiate same as purchase of the decision, and loyalty.